Maternal Outcomes in Pregnant Women with Uterine Fibroids - Gul, Fazeela; Liaqat, Nazia; Anila (Indus Journal of Bioscience Research, 2025)
Background: Uterine fibroids are described as benign tumors of the uterine commonly arise in reproductive-age women group. During pregnancy due to hormonal and vascular alterations may produce fibroid enlargement and complications that affect the mother’s health. They can be excessive postpartum bleeding, premature labor and anemia and affect the mother’s comfort and recovery. Understanding these outcomes in local populations is essential for improving obstetric care, particularly in regions with limited resources and delayed antenatal follow-up. Objective: To determine the maternal outcome in pregnant women with uterine fibroids. Study Design: Cross-sectional study. Duration and Place of Study: This study was conducted from March 2024 to August 2024 in the Department of Obstetrics and Gynecology, Lady Reading Hospital Peshawar. Methodology: Eighty-one pregnant women aged 18–40 years with confirmed uterine fibroids were included through non-probability consecutive sampling. Data were collected using a structured proforma. Postpartum hemorrhage was defined as blood loss greater than 500 milliliters after delivery, preterm delivery as birth before 37 weeks, and anemia as hemoglobin less than 12 grams per deciliter. Results: Postpartum hemorrhage was found in 17.30% of participants, preterm delivery in 9.90%, and anemia in 14.80%. The majority of participants were from middle socioeconomic backgrounds and rural areas. Conclusion: Pregnant women with uterine fibroids are at higher risk of postpartum bleeding, early delivery, and anemia.